Pelatihan Membangun Tim Unggul di Era Digital: Solusi Pertumbuhan BerkelanjutanUntuk UMKM Hijab (Pada C.V Syamil Hijab di Cicalengka) - Fauzan Manafi Albar; Cucu Hodijah; Hasti Pramesti Kusnara; Umban Adi Jaya; Sofia Dewi (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
The development of the digital era requires Micro, Small, and Medium Enterprises (MSMEs) to improve their competitiveness not only from a technological aspect, but also from the quality of human resources (HR). One of the main problems faced by MSMEs is the suboptimal management of effective, communicative, and adaptive work teams. CV Syamil, with 42 employees, as an MSME in the Muslim fashion sector, faces challenges in strengthening Teamwork and leadership. This community service activity aims to improve HR capacity through training to build superior teams that include effective communication, Teamwork, and leadership. The methods used are training, discussion, and Mentoring. The results of the activity show an increase in participants' understanding of Teamwork, organizational communication, and leadership. The impact of the activity is seen in increased work coordination and HR readiness to face changes in the digital era. Thus, strengthening HR is a key factor in supporting the sustainable growth of MSMEs.